2014
DOI: 10.1177/000313481408001006
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Follow-up of Breast-conserving Therapy in Patients with Inflammatory Breast Cancer Treated with Neoadjuvant Chemotherapy

Abstract: Inflammatory breast cancer (IBC) is a rare and aggressive form of breast cancer. Currently, multimodality treatment is recommended, but the optimal surgical management has not been fully elucidated. In this study, we investigated the long-term outcomes of using breast-conserving therapy in patients with IBC undergoing neoadjuvant chemotherapy (NAC). Twenty-four patients with IBC were treated from 2002 to 2006. NAC was initiated with doxorubicin and cyclophosphamide followed by paclitaxel. In addition, HER2/neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 10 publications
(13 reference statements)
0
19
0
Order By: Relevance
“…MR imaging is routinely used to monitor treatment response to neoadjuvant chemotherapy. Studies have suggested a correlation between various MR imaging parameters, such as baseline morphologic features, functional tumor volume, background parenchymal enhancement, and pCR in patients with HER2-positive breast cancer (23)(24)(25)(26)(27). These studies show good results, with some suggestion that MR imaging is more accurate in predicting pCR in ER-negative tumors (28).…”
Section: Discussionmentioning
confidence: 99%
“…MR imaging is routinely used to monitor treatment response to neoadjuvant chemotherapy. Studies have suggested a correlation between various MR imaging parameters, such as baseline morphologic features, functional tumor volume, background parenchymal enhancement, and pCR in patients with HER2-positive breast cancer (23)(24)(25)(26)(27). These studies show good results, with some suggestion that MR imaging is more accurate in predicting pCR in ER-negative tumors (28).…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that partial mastectomy is associated with poorer survival contrasts with two small reports on breast conservation therapy in women with IBC. Bonev and colleagues [ 11 ] retrospectively analyzed a series of 24 patients with IBC and found no significant difference in overall survival at median follow-up of 60 months between women who underwent partial mastectomy versus total mastectomy following neoadjuvant chemotherapy (overall survival 59% versus 57%, 0.49). Similarly, in a retrospective single-institution analysis, Brzezinska and colleagues [ 12 ] found that 35 women with IBC treated with breast conservation surgery had similar rates of locoregional control and survival compared with those treated with mastectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the addition of locoregional therapy to anthracycline-based chemotherapy impacts survival in IBC remains controversial, especially the extent of surgery [ 10 ]. Several authors [ 11 , 12 ] have reported similar survival rates in small cohort studies with patients who underwent breast conserving surgery when compared to patients who underwent total mastectomy after preoperative systemic therapy and have questioned whether IBC is an absolute contraindication to breast conservation therapy. However, these reports are from single institutions and have a small sample size.…”
Section: Introductionmentioning
confidence: 99%
“…This cohort represents a selected subset of patients diagnosed with IBC with low disease burden. Case selection is likely to have a bearing on several other reported series where a breast conservation approach was used 40 , 41 . In large retrospective series the outcome after a conservative approach appears inferior, although again the caveats of retrospective studies are acknowledged 42 .…”
Section: Introductionmentioning
confidence: 99%